Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Yang Dimediasi Oleh Motivasi Dan Kepuasan Kerja - RD. Ainun Nur Azizah; Sudirman Zaid; Sri Wiyati Maharani; Usman Usman; Wade Rahma Batin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of work discipline on work motivation, job satisfaction, and employee performance, as well as the mediating role of motivation and job satisfaction at the Regional Secretariat of Konawe Regency. The study involved 186 employees as the research population, and data were analyzed using path analysis with Partial Least Square (PLS) assisted by SmartPLS software. The findings reveal that work discipline has a positive and significant effect on work motivation, job satisfaction, and employee performance. Furthermore, work motivation and job satisfaction also have a positive and significant effect on employee performance. The results further indicate that both work motivation and job satisfaction significantly mediate the relationship between work discipline and employee performance. These findings highlight that improving employee performance requires not only strong work discipline but also enhanced motivation and job satisfaction.